Bioaccessibility versus bioavailability of essential (Cu, Fe, Mn, and Zn) and toxic (Pb) elements from phyto hyperaccumulator Pistia stratiotes: potential risk of dietary intake - Čadková, Zuzana; Száková, Jiřina; Miholová, Daniela; Horáková, Barbora; Kopecký, Oldřich; Křivská, Daniela; Langrová, Iva; Tlustoš, Pavel (Journal of agricultural and food chemistry, 2015)
Aquatic weeds are widely used as animal feed in developing countries. However, information about element bioavailability from these plants is lacking. A combination of an in vitro method [physiologically based extraction test (PBET)] and an in vivo feeding trial was used in this study to investigate potential element bioaccessibility and estimated bioavailability of Pistia stratiotes (PS). Cu, Fe, Mn, Zn, and Pb concentrations in PS biomass, artificial gastrointestinal fluids, and rat tissues were determined using atomic absorption spectrometry with electrothermal atomization and inductively coupled plasma-atomic emission spectrometry. PS exhibited elevated Fe, Mn, and Pb levels. The PBET revealed high bioaccessibility of all monitored elements from PS biomass. The results of the in vivo trial were inconsistent with those of the PBET, because animals fed PS exhibited low levels of essential elements in the tissues. The consumption of a PS-supplemented diet significantly decreased total Fe levels and increased the total level of accumulation of Pb in exposed animals. Significantly reduced amounts of essential elements in the intestinal walls indicated a potential disruption in nutrient gastrointestinal absorption in animals fed PS.
Keywords: Araceae; mangan; Rats; látky znečišťující půdu; Zinc; feeding trial; Copper; krmivo pro zvířata; microelements; olovo; biokinetics; mužské pohlaví; měď; železo; physiologically based extraction test; Manganese; Lead; risk elements; krysa rodu Rattus; Soil Pollutants; Iron; zvířata; anatomické struktury zvířat; Animal Feed; zinek; Pistia stratiotes; Animal Structures; Male; Animals